What’s in a name? Memory NK cells for cancer immunotherapy - William J Murphy; Robert J Canter; Sean J Judge; Megan C Purl (Journal for ImmunoTherapy of Cancer)
The discovery that natural killer (NK) cells can retain features of “memory” from previous stimulation and pathogen exposure was a landmark advance highlighting one of many ways in which NK cells of the innate immune system resemble T cells of the adaptive immune system. This ability to “remember” prior stimulation to bring about enhanced protection of the host sparked significant excitement regarding potential therapeutic applications. Yet, how closely the features of naïve and memory NK cells recapitulate those of T cells remains unclear. Nonetheless, despite unresolved questions about the immunobiology of naïve and memory NK cells, the application of memory NK cells to the clinic for cancer and other indications has gathered steam to meet the unmet need for novel immunotherapies. Recent work from Arellano-Ballestero et al highlights this evolving field and the current state of the art with memory NK cells. Application of these cells to the clinic is progressing with promising results, but important questions remain about the essential molecular, phenotypic, and functional characteristics that define a memory NK cell.